Cardiac rehabilitation in people with peripheral arterial disease: A higher risk population that benefits from completion. (15th June 2019) - Devrome, Andrea N.; Aggarwal, Sandeep; McMurtry, M. Sean; Southern, Danielle; Hauer, Trina; Lamb, Brea; Arena, Ross; Moore, Randy D.; Wilton, Stephen B.; Stone, James; Martin, Billie-Jean
Abstract: Background: Peripheral arterial disease (PAD) is common in people referred for cardiac rehabilitation (CR). However, the associations between PAD diagnosis and CR attendance and mortality remain to be defined. Methods: All patients referred to a 12-week exercise-based CR program were included. Associations between PAD diagnosis and starting CR as well as between PAD diagnosis and completing CR were measured using multivariable logistic regression. Associations between CR completion and mortality were measured using adjusted Cox proportional hazards models, and a propensity-based matching sensitivity analysis was performed. Results: 23, 215 patients (mean age 61.3 years; 21.6% female) were referred to CR; 1366 (5.9%) had PAD. Those with PAD were less likely to start CR (57.0% vs 68.2%, adjusted OR 0.81, 95%CI 0.72, 0.91) and complete CR if they started (70.6% vs 76.7%, adjusted OR 0.80, 95%CI 0.68, 0.94). Patients with PAD completing CR had lower exercise capacity at baseline (6.6 vs. 7.6 METs, p  < 0.0001) and completion (7.5 vs 8.6 METs, p  < 0.0001). There were 3510 deaths over follow-up; 10-year survival was lower in those with PAD (66.9 vs 84.5%; p  < 0.0001). CR completion was associated with lower mortality for all (adjusted HR 0.62 (95%CI 0.57, 0.67)), and the magnitude of the association was independent of PAD status. Conclusions: Patients with PAD referred to CR had a higher mortality than those without, and were less likely to start and complete CR. Completion of CR was associated with improved fitness and survival for PAD patients. These data support broader use of CR by those with PAD. Highlights: Peripheral arterial disease is common in people referred for cardiac rehabilitation Subjects with peripheral arterial disease are less likely to participate in cardiac rehabilitation Subjects with peripheral arterial disease have significantly lower exercise capacity at baseline than those without Survival is significantly better when completing rehabilitation, even with a peripheral arterial disease diagnosis.